Komunikasi Organisasi Pada Organisasi Masyarakat/Ormas di Jakarta: Studi Kasus Forum Betawi Rempug - Lerman Sinaga (Brand Communication, 2022)
FBR was the biggest local mass organization in Jakarta, Indonesia. Existence of FBR to show active people participate for development process in country. It is shows us how the real democrate process happened in Indonesia. History about FBR people always give identify Betawi as the group of people in Jakarta. This research problem was how identity FBR as mass organization in this era? The theoretical studies of this research were organization, organization communication, organization communication cultural studies. Methodology this research use interpretive and qualitative data processing. Depth interview use with FBR members in Jakarta. Finding show that FBR moving has change from anti immigrant (FBR see immigrant was colonialist) to justice for all people in Jakarta. Beside that FBR also was struggling live people economy for Betawi people.